The South African income tax implications of a Stokvel - Matshego, Katlego (Rhodes University, Faculty of Commerce, Department of Accounting, 2020)
The term "Stokvel" originates from the rotating cattle auctions of English settlers in the Eastern Cape during the nineteen century. A Stokvel is defined as a credit union where a group of people agree to contribute a fixed amount of money to a common pool and is referred to as a rotating savings and credit association, where the contributions to a fund are given in whole or in part to each member. The goal of the thesis was to determine the "gross income" implications of the fund and its members, as well the deductibility of their expenses. An interpretative research approach was used in the research as it sought to understand and describe. No interviews were conducted for this research and the data used for the research are publicly available. The tax implications of five different types of a Stokvel were considered in relation to the research goals through the application of legislation and case law principles. The study established that a collection burial society, where funds are contributed after death, does not beneficially receive funds and it is not entitled to any deductions. The same applies to the member of that society. A contributing burial society, where funds are contributed over time, beneficially receives funds, which are included in "gross income" , and qualifies for deductions. The receipt by the member is exempt and deductions are prohibited by section 23(f). An entertainment Stokvel does not receive the contributions on its own behalf and benefit. No deductions are available to it. However, the member beneficially receives the contributions from the Stokvel, which are included in "gross income" , and qualifies for deductions. A purchasing power group, where items are purchased on behalf of members, does not receive the funds beneficially and no deductions are available to it. The members simply receive the goods they have paid for. Lastly an investment Stokvel, which invests contributions for the members, beneficially receives contributions and qualifies for various deductions. The member receives the share of income from the Stokvel for his/her own benefit. However, no deductions are available in respect of contributions.
Keywords: Rotating credit associations -- South Africa.; Taxation -- South Africa; Tax deductions -- South Africa